TURKIC SULTANATES AND FEMALE SOVEREIGN IN ISLAMDOM - Hanafi Wibowo (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2016)
The status of women in the Islamdom is a source of frequent criticism. Some Western critics charge that Islam has misogynist tendencies that are often teaches and promoted the inferiority of women in Muslim societies. As a result the debate over female leadership in Islam is a become splinter of the debate on Islam’s views of women in general. The role of Women in Islam, as a political leader is considered a taboo, even sometimes get fierce opposition from a group of people, who interpret the word of God in a veil of monopolistic desires. However, there were numerous women in Islamic history that is capable of being head of state. In the various Arab speaking notes, women have been known as the head of state. In the Sultanate of Delhi, there was Razia Sultan, in Egypt there was Shajarat ad Durr, during Ottoman period, there was Mihrimah Sultan and coincidently, all of them were Turkic origin. The study examines the reason why those women can become leaders within Islamdom. The conclusion, secularism of Islamdom which orchestrated by Turkic Mercenaries, when the institution of Abbasid Caliphate and Sultanate was separated, makes the women are eligible to become sultanah, which consistent with women’s independent nature in Turkic society.Status perempuan di dunia Islam merupakan masalah yang kerapkali diperdebatkan. Beberapa kritikus Barat menuduh bahwa Islam memiliki kecenderungan misoginis yang sering mengajarkan rendahnya posisi perempuan dalam masyarakat Muslim. Akibatnya perdebatan kepemimpinan perempuan dalam Islam selalu mengarah menjadi perdebatan pada pandangan Islam tentang perempuan pada umumnya. Peran perempuan dalam Islam, sebagai pemimpin politik dianggap tabu, bahkan kadang-kadang mendapatkan perlawanan sengit dari sekelompok orang, yang menafsirkan firman Allah sesuai keinginannya sendiri. Namun, ada banyak perempuan dalam sejarah Islam yang mampu menjadi kepala negara. Dalam berbagai catatan berbahasa Arab, perempuan telah dikenal sebagai pemimpin negara. Di Kesultanan Delhi ada Razia Sultan, di Mesir ada Syajarat al Durr, di Turki Usmaniada Mihrimah Sultan dan kebetulan semua dari orang Turki. Artikel ini mengkaji alasan mengapa para perempuan dapat menjadi pemimpin di dunia Islam. Kesimpulannya, sekularisme di dunia Islam yang dilakukan oleh para tentara bayaran Turki mengakibatkan terjadinya separasi antara institusi Kekhalifahan Abbasiyah dan kesultanan yang memungkinkan perempuan untuk menjadi seorang sultanah serta konsisten dengan sifat perempuan yang mandiri dalam masyarakat Turki.